Microsurgical Clipping of Unruptured Middle Cerebral Artery Bifurcation Aneurysms: A Single-Center Experience - Nico Stroh-Holly; Philip Rauch; Harald Stefanits; Philipp Hermann; Helga Wagner; Michael Sonnberger; Maria Gollwitzer; Stefan Aspalter; Andreas Gruber; Matthias Gmeiner (Brain Sciences)
Background/Objectives: Microsurgical clipping has traditionally been considered a standard treatment for middle cerebral artery (MCA) aneurysms. Recently, a caseload reduction related to improved endovascular treatment options has occurred in cerebrovascular neurosurgery. Therefore, studies that report the clinical and radiological outcomes after clipping are highly warranted. Methods: Patients with an unruptured MCA bifurcation aneurysm, who were surgically treated at the Department of Neurosurgery in Linz between 2002 and 2019, were included in this study. Clinical and radiological outcome parameters were evaluated for each patient. Results: Overall, 272 patients were eligible for inclusion. Complete aneurysm occlusion was demonstrated in 266 (99.3%) of the 268 (98.5%) patients who underwent postoperative digital subtraction angiography. In six (2.2%) patients, a permanent new neurological deficit (pNND) persisted after treatment. Intraoperative aneurysm rupture was a significant factor (p = 0.0049) in the logistic regression. At the last follow-up, only two patients (0.7%) had an unfavorable outcome (mRS > 2). More recent surgeries were associated with fewer cases of pNND (p = 0.009). A transient new neurological deficit occurred in 13 patients (4.8%), with aneurysm size being a significant risk factor (p = 0.009). Surgical site infections were reported in four patients (1.5%), with patient age (p = 0.039) and time (p = 0.001) being significant factors. Two patients died (0.7%) perioperatively and two patients (0.7%) needed a retreatment in the long-term follow-up. Conclusions: The findings indicate that microsurgical clipping is a safe procedure with minimal need for retreatment. It achieves a high occlusion rate while maintaining a very low rate of adverse outcomes. Continuous intraoperative enhancements over time have contributed to a progressive improvement in clinical outcomes in recent years. This trend is exemplified by the absence of detectable pNND in the era of ICG angiography. Consequently, these data support the conclusion that microsurgical clipping should still be considered an appropriate treatment option for unruptured MCA bifurcation aneurysms.